Analisis Fiqih Muamalah dalam Transaksi Jual Beli Online Menurut Perspektif Hukum Islam dan Syariah - Adil Alfarizi Nst; Imsar Imsar (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study employs a qualitative library research method with the aim of analyzing fiqh muamalah in the practice of online buying and selling transactions from the perspective of Islamic law and sharia. The development of digital technology has given rise to various new models of transactions that require Islamic law to remain adaptive and relevant. Online trade is one form of contemporary muamalah that raises several issues, such as the validity of contracts, price transparency, clarity of goods, and the potential for fraud. In fiqh muamalah, the validity of a sale and purchase contract is determined by the fulfillment of its pillars and conditions, namely the presence of contracting parties, a clearly defined object of transaction, and a legitimate agreement. The findings indicate that online buying and selling transactions are valid as long as they comply with sharia principles such as justice, transparency of information, clarity of goods, and the absence of gharar (uncertainty), maysir (gambling), or riba (usury). Thus, Islamic law does not reject technological innovation as long as the substance of the contract remains in line with sharia. This research emphasizes that fiqh muamalah is capable of providing practical and relevant solutions in addressing the challenges of the modern digital economy.